Temporal and spatial variability of immunosuppressive therapies in transplant patients: An observational study in Italy - Marino, Maria Lucia; Rosa, Alessandro C.; Finocchietti, Marco; Bellini, Arianna; Poggi, Francesca R.; Massari, Marco; Spila Alegiani, Stefania; Masiero, Lucia; Ricci, Andrea; Bedeschi, Gaia; Puoti, Francesca; Cardillo, Massimo; et al. (Frontiers in Transplantation, 2023)
Background In immunosuppression after transplantation, several multi-drug approaches are used, involving calcineurin inhibitors (CNI: tacrolimus-TAC or cyclosporine-CsA), antimetabolites (antiMs), mammalian target of rapamycin inhibitors (mTORis), and corticosteroids. However, data on immunosuppressive therapy by organ and its space–time variability are lacking. Methods An Italian multicentre observational cohort study was conducted using health information systems. Patients with incident transplant during 2009–2019 and resident in four regions (Veneto, Lombardy, Lazio, and Sardinia) were enrolled. The post-transplant immunosuppressive regimen was evaluated by organ, region, and year. Results The most dispensed regimen was triple-drug therapy for the kidneys [tacrolimus (TAC) + antiM + corticosteroids = 41.5%] and heart [cyclosporin + antiM + corticosteroids = 36.6%] and double-drug therapy for liver recipients (TAC + corticosteroids = 35.4%). Several differences between regions and years emerged with regard to agents and the number of drugs used. Conclusion A high heterogeneity in immunosuppressive therapy post-transplant was found. Further studies are needed in order to investigate the reasons for this variability and to evaluate the risk–benefit profile of treatment schemes adopted in clinical practice.